2020
DOI: 10.1136/annrheumdis-2020-217763
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hospital PCR-confirmed COVID-19 cases in patients with chronic inflammatory and autoimmune rheumatic diseases

Abstract: BackgroundThe susceptibility of patients with rheumatic diseases and the risks or benefits of immunosuppressive therapies for COVID-19 are unknown.MethodsWe performed a retrospective study with patients under follow-up in rheumatology departments from seven hospitals in Spain. We matched updated databases of rheumatology patients with severe acute respiratory syndrome coronavirus 2-positive PCR tests performed in the hospital to the same reference populations. Rates of PCR+ confirmed COVID-19 were compared amo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
127
4
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(152 citation statements)
references
References 15 publications
10
127
4
11
Order By: Relevance
“…Currently available data do not imply a strikingly increased risk of infection for RMD with or without DMARD therapy in general ( 51 , 52 ), although differences in the individual diseases have been reported ( 53 ). Pablos et al investigated the prevalence of COVID-19 in seven Spanish hospitals providing medical care for a population of 2.9 million patients, and found a comparable prevalence of the infection in RA and PsoA with the general population (0.58%); in contrast, patients with spondylarthritis (SpA) had a higher prevalence ( 53 ). As this was also the case for patients on bDMARDs or JAKi, one might speculate that the higher infection rate of SpA patients was due to a higher percentage of these drugs in SpA patients compared to the other groups.…”
Section: Rheumatic Diseases and Covid-19mentioning
confidence: 99%
“…Currently available data do not imply a strikingly increased risk of infection for RMD with or without DMARD therapy in general ( 51 , 52 ), although differences in the individual diseases have been reported ( 53 ). Pablos et al investigated the prevalence of COVID-19 in seven Spanish hospitals providing medical care for a population of 2.9 million patients, and found a comparable prevalence of the infection in RA and PsoA with the general population (0.58%); in contrast, patients with spondylarthritis (SpA) had a higher prevalence ( 53 ). As this was also the case for patients on bDMARDs or JAKi, one might speculate that the higher infection rate of SpA patients was due to a higher percentage of these drugs in SpA patients compared to the other groups.…”
Section: Rheumatic Diseases and Covid-19mentioning
confidence: 99%
“…A large-scale study from the UK showed that common autoimmune diseases such as RA and SLE were risk factors for COVID-19 related death [150]. Moreover, compared with the reference population, COVID-19 has occurred more frequently in patients with rheumatic diseases (odds ratio 1.32, 95% CIs 1.15∼1.52), especially in patients receiving bDMARDs or tsDMARDs as reported in a Spanish retrospective study conducted in seven hospitals [151]. COVID-19 is a highly infectious disease, especially during the early stage, and is associated with significant morbidity and fatality rates.…”
Section: Resultsmentioning
confidence: 91%
“…The risk was similar to general population in patients with SLE and was higher in other systemic autoimmune diseases. 12 The severity of COVID-19 in RD seems to be similar to the general population. 10 A global rheumatology alliance that included 600 patients (70% female) of RD from multiple centers found a mortality of 9% in a patients with RD and COVID-19.…”
Section: Covid-19 In Rheumatic Diseases (Rd)mentioning
confidence: 78%